2016
DOI: 10.4196/kjpp.2016.20.5.515
|View full text |Cite
|
Sign up to set email alerts
|

Molecular association of CD98, CD29, and CD147 critically mediates monocytic U937 cell adhesion

Abstract: Adhesion events of monocytes represent an important step in inflammatory responses induced by chemokines. The β1-integrin CD29 is a major adhesion molecule regulating leukocyte migration and extravasation. Although several adhesion molecules have been known as regulators of CD29, the molecular interactions between CD29 and its regulatory adhesion molecules (such as CD98 and CD147) have not been fully elucidated. Therefore, in this study, we examined whether these molecules are functionally, biochemically, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…For direct evidence about whether Src bound its substrates p85 or STAT3, we used immunoprecipitation. Whole cell lysates with increased activated p85 and STAT3 were from LPS-treated RAW264.7 cells, according to previous reports [ 23 ]. ARP at 50 µM blocked binding of p85 to Src.…”
Section: Resultsmentioning
confidence: 99%
“…For direct evidence about whether Src bound its substrates p85 or STAT3, we used immunoprecipitation. Whole cell lysates with increased activated p85 and STAT3 were from LPS-treated RAW264.7 cells, according to previous reports [ 23 ]. ARP at 50 µM blocked binding of p85 to Src.…”
Section: Resultsmentioning
confidence: 99%
“…The β 1 integrin CD29 plays an important role in the regulation of cell attachment and migration of immune cells in inflammatory processes ( 34 ). Although the molecular regulation of CD29 has not been fully elucidated yet, it has been suggested that it might be modulated by its regulatory adhesion molecules CD98 (a cell-surface glycoprotein) and CD147 (basigin; glycoprotein coreceptor) via the actin cytoskeleton ( 35 ). Furthermore, it has recently been shown that inhibition of the integrin β1/PYK2 axis has a negative impact on the transendothelial migration of monocytes, as well as the cancer-promoting functions of tumor-associated macrophages ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wanted to investigate regions of CD147 that could be involved with (1) the stabilization of L. monocytogenes membrane protrusions and (2) the potential recruitment of CypA to the structures. To do this, we treated infected cells with a CD147 blocking antibody (called MEM-M6/1) that targets the N-terminal Ig domain of the protein [23,24]. We added the CD147 blocking antibody (vs normal mouse IgG [control]) to wild-type host cells 2 h post-infection and allowed the infections to proceed for an additional 5 h to observe membrane protrusions.…”
mentioning
confidence: 99%